The Effect of Accent Thai on English Students’ Pronunciation at Masjid Taluban School Sai Buri Thailand - Solidha Ramadiah Harahap; Rahmat Huda; Akhmad Tarmizi Lubis; Eli Marlina Harahap; Mukhlis (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the influence of Thai accent on the English pronunciation of fifth-grade students at Masjid Taluban School, Sai Buri, Thailand. Reading test analysis identified five main error patterns: 1) substitution of /v/ to /w/ or /b/; /θ/ to /t/, /s/; 2) loss of final consonant /t/; 3) addition of vowel at the junction of two consonants; and 4) pronunciation of /r/ that is not firm and some words change to /l/. This study used a qualitative descriptive approach involving 30 students as research subjects. The instruments used included a placement test in the form of 30 multiple-choice items and 10 essay items, a reading test, and a structured interview. The results showed that 30% of students were in the fair category, 23% in the needs improvement category, 27% in the good category, 10% in the very good category, and only 10% of students reached the excellent category. These findings confirm the existence of Thai phonological interference on English pronunciation, especially on sounds that are not included in the Thai phonological system. The results of the study indicate that Thai accents influence students' English pronunciation. The implication of this research is the need for pronunciation teaching strategies that consider the phonological characteristics of students' first languages ​​to improve English pronunciation.